Bangladesh agricultural sustainability: Economic, environmental and social issues - Salim, Ruhul; Noor-E-Sabiha; Rahman, S. (2018)
This chapter examines the potential for agricultural sustainability in Bangladesh mainly by analyzing economic, environmental and social issues at the macro-level. The economic issues were examined by assessing the contribution of the agricultural sector to Gross Domestic Product (GDP), trends in cereal yield, employment of the labor force in agriculture and domestic food price index covering a 38-year period (1980-2017). The environmental issues were examined by assessing the use of chemical fertilizers, pesticides, irrigation, cropping intensity and CO 2 emission from agriculture over time (1990-2015). The social context of agricultural sustainability were analyzed by examining attributes such as encroachment of arable land for urbanization and other industrial uses, unavailability of arable land, trends in increase in import of food grains and variability in food production. Results revealed that all of these issues adversely affected future agricultural productivity, thereby casting doubt on the sustainability of agriculture in Bangladesh. Despite having increasing trend in cereal yield since 1980s, the contribution of agriculture sector to the GDP was found to be decreasing over time. Also the proportion of working age population engaged in agriculture sector was declining over the last forty years. Furthermore, variability in food production and increasing domestic food price index affected food stability. Bangladeshi farmers are losing valuable arable land at a rate of 0.3% p.a., which may have influenced increase in cropping intensity at a rate of 0.6% p.a. since 1980's. Increasing trend in low-cost food grain import reflects changing preference of the consumers. The use of chemical fertilizer is increasing at a rate of 2.5 kg/ha p.a., which may be a principal factor in increasing CO 2 emissions from agriculture at a rate of 1.1% p.a. since 1990's. Among the selected indicator variables, a high uncertainty for sustainability in agriculture was found from falling agricultural value added to the GDP and use of chemical pesticides, while moderate uncertainty for sustainability was found for other indicator. The environment friendly agricultural practice can play a vital role in achieving agricultural sustainability in the long-run. Policy reforms are required with respect to subsidies in agriculture and the use of farm chemicals in order to improve agricultural productivity and limit adverse environmental impacts from agriculture.